NaLuF4: Tb, Dy dosage tablet and preparation method thereof
NaLuF4:Tb, Dy dose tablets were prepared through improved low-temperature ligand-free hydrothermal synthesis method, which solved the problems of unmodified luminescence peak temperature, poor energy response and complex process of existing thermoluminescence dose tablets, and achieved high sensitivity It has stable thermal light-emitting performance, simple process and low cost, and is suitable for the field of solid thermal light-emitting dose monitoring.
Patent Information
- Application Number
- CN202411477012.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-14
AI Technical Summary
The existing thermoluminescent dose sheets have problems such as uncomfortable luminescence peak temperature, poor energy response, complex process and high cost. In particular, lithium fluoride series materials are mainly in powder form and are inconvenient to process, and the main luminescence peak of calcium sulfate series The temperature is low and the thermal light emission signal is severely decayed, the thermal light emission performance of the calcium fluoride series is unstable, and the thermal light sensitivity of the lithium borate series is not high.
NaLuF4:Tb, Dy is used as the thermoluminescent material, and the high sensitivity and moderate luminescence peak temperature are prepared by improved low-temperature ligand-free hydrothermal synthesis method to obtain NaLuF4:Tb, Dy dose tablets with high sensitivity and moderate luminescence peak temperature. The main body is tetrafluorogenic sodium, and the total number of Doping with two rare earth elements, terbium and dysprosium, NaLuF4:Tb and Dy powder materials are prepared through hydrothermal reaction and formed into sheet-like dose tablets.
It has achieved a high sensitivity and moderate luminescence peak temperature. It has a large linear range, good energy response, long-term reuse and stable luminescence. It has a simple and efficient preparation process, high cost-effectiveness, and environmentally friendly.
Smart Images

Figure CN119306244A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of radiation dose sheets, and in particular to a NaLuF4:Tb,Dy dose sheet and a preparation method thereof. Background Art
[0002] Thermoluminescence is a phenomenon in which semiconductor materials or insulators are heated and emit light after absorbing radiation in advance. The radiation dose in a certain area can be measured based on the amount of light emitted. At present, monitoring the radiation dose received by people in special occupations is one of the routine tasks carried out by disease prevention and control centers at all levels in my country. Thermoluminescent dosimeters made of thermoluminescent materials can be widely used in many fields such as radiation therapy, radiation protection, geological age measurement, environmental monitoring, archaeology, and aerospace.
[0003] The principle of thermoluminescent dosimeter to detect radiation dose is: in the process of thermoluminescence, when an insulator or semiconductor is irradiated by external high-energy radiation, electrons are excited from the valence band to the conduction band. Some electrons return to the valence band in a very short time, and some electrons may stay in the trap energy levels in the forbidden band (these trap energy levels may be formed by impurities and solid defects, etc.). If there is no thermal disturbance, the electrons in the trap energy levels will not return to the valence band. The more electrons in the trap energy levels, the higher the accumulated radiation dose of the object. Using this characteristic, the accumulated radiation dose of the object can be measured, so as to determine the accumulated radiation dose of the human body in the same radiation environment.
[0004] The luminescence curve is a curve showing the change of thermoluminescence intensity with temperature. Information on radiation dose is usually obtained from the integrated area under the luminescence curve. In other words, because the area of the luminescence curve represents the amount of luminescence, and the amount of luminescence is proportional to the radiation dose, the area of the luminescence curve is proportional to the accumulated radiation dose.
[0005] In the 1950s, F. Daniels of the University of Wisconsin in the United States first proposed that thermoluminescence could be used as a method for radiation dose measurement, and used the thermoluminescence properties of LiF for monitoring radiation doses in atomic bomb fields and for measuring internal radiation doses in cancer patients treated with radioactive isotopes. Currently, there are many commonly used thermoluminescent materials, including lithium fluoride with different doping (LiF:Mg,Cu,P and LiF:Mg,Ti), calcium sulfate (CaSO4:Mn and CaSO4:Dy), calcium fluoride (CaF2:Mn and CaF2:Dy), lithium borate (Li2B4O7:Mn and Li2B4O7:Cu,Ag), magnesium silicate (MgSiO4:Tb and MgSiO4:Tb,Na), aluminum oxide (α-Al2O3:C and α-Al2O3:Cr) Series such as the Chinese invention patent with application number 202010125365.2 discloses a thermoluminescent detection material and its preparation method, including 90-110 parts by weight of lithium fluoride, 0.2-1.5 parts by weight of calcium oxide, 0.05-0.12 parts by weight of magnesium oxide, 0.02-0.1 parts by weight of copper oxide and 0.06-0.15 parts by weight of phosphorus pentoxide, which can effectively improve the luminescence curve characteristics of the thermoluminescent detection material. However, these materials all have their own shortcomings. For example, the main disadvantage of the lithium fluoride series is that the material mainly exists in the form of powder, which is not convenient for processing and annealing; the main luminescence peak temperature of the calcium sulfate series is low, and the thermoluminescent signal decays seriously; the thermoluminescent performance of the calcium fluoride series is unstable and the light-induced decay is very serious; the thermoluminescent sensitivity of the lithium borate series is not high. In addition, they generally have problems such as complex preparation process, high cost, and luminescent wavelength in the near ultraviolet. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a NaLuF4:Tb,Dy dosage sheet with moderate luminescence peak temperature, good energy response and simple and efficient process and a preparation method thereof.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a NaLuF4:Tb,Dy dosage tablet, comprising the following steps: S1, mixing a rare earth salt and water to obtain a rare earth salt solution, then mixing the rare earth salt solution with a fluoride to obtain a mixed solution, adjusting the pH value of the mixed solution to neutral, and then adding an alcohol solvent to perform a hydrothermal reaction to obtain a NaLuF4:Tb,Dy powder material; S2. Form NaLuF4:Tb,Dy powder material into sheets to obtain NaLuF4:Tb,Dy dosage sheets.
[0008] Another technical solution adopted by the present invention is: the NaLuF4:Tb,Dy dosage tablet is prepared by adopting the above-mentioned preparation method of the NaLuF4:Tb,Dy dosage tablet.
[0009] The beneficial effects of the present invention are as follows: the present invention uses sodium lutetium tetrafluoride as the main component, co-doped with two rare earth elements, terbium and dysprosium, and prepares a NaLuF4:Tb,Dy dose sheet with high sensitivity, moderate luminescence peak temperature, large linear range, good energy response, long-term reusability and stable luminescence through an improved low-temperature ligand-free hydrothermal synthesis method. The preparation process is simple, efficient, cost-effective and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 Shown is a thermoluminescence mechanism diagram of a NaLuF4:Tb,Dy dosing sheet according to a specific embodiment of the present invention; Figure 2 The figure shows a process flow chart of preparing the NaLuF4:Tb,Dy dosage sheet of Example 1 of the present invention; Figure 3 The figure shows a real picture of NaLuF4:Tb,Dy powder material of Example 1 of the present invention; Figure 4 Shown is a scanning electron microscope image of the NaLuF4:Tb,Dy powder material of Example 1 of the present invention; Figure 5 The figure shows a physical picture of the NaLuF4:Tb,Dy dosage sheet of Example 1 of the present invention; Figure 6 The figure shows a thermoluminescent photograph of the NaLuF4:Tb,Dy dosage sheet of Example 1 of the present invention; Figure 7 The thermoluminescence curve of a conventional LiF:Mg,Cu,P dosimeter under X-ray irradiation Figure 8 The figure shows the thermoluminescence curve of the NaLuF4:Tb,Dy dose sheet of Example 1 of the present invention under X-ray irradiation; Fig. 9 The figure shows a comparison of the dose response curves of the NaLuF4:Tb,Dy dose sheet of the first embodiment of the present invention and the conventional LiF:Mg,Cu,P dose sheet. DETAILED DESCRIPTION
[0011] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.
[0012] Please refer to Figure 2 , a method for preparing a NaLuF4:Tb,Dy dosage tablet, comprising the following steps: S1, mixing a rare earth salt and water to obtain a rare earth salt solution, then mixing the rare earth salt solution with a fluoride to obtain a mixed solution, adjusting the pH value of the mixed solution to neutral, and then adding an alcohol solvent to perform a hydrothermal reaction to obtain a NaLuF4:Tb,Dy powder material; S2. Form NaLuF4:Tb,Dy powder material into sheets to obtain NaLuF4:Tb,Dy dosage sheets.
[0013] From the above description, it can be seen that the present invention uses sodium lutetium tetrafluoride (NaLuF4) as the main body, co-doped with two rare earth elements terbium (Tb) and dysprosium (Dy), and prepares NaLuF4:Tb,Dy dose tablets through an improved low-temperature ligand-free hydrothermal synthesis method. The preparation process is simple, the yield is high, the reproducibility is good, the preparation method is green and environmentally friendly, and there is no toxic and harmful gas emission. The prepared NaLuF4:Tb,Dy dose tablet has good dispersibility, excellent fluorescence intensity and long-lasting long afterglow luminescence performance, and is highly sensitive to X-rays, showing extremely excellent sensitivity, which is 64 times the highest sensitivity of the LiF:Mg,Cu,P thermoluminescent dose tablet widely used in the market, and has good application value in the field of solid thermoluminescent dose monitoring.
[0014] Please refer to Figure 1 The principle of thermoluminescence of NaLuF4:Tb,Dy dosimeter is as follows: X-ray energy is mainly absorbed by Lu atoms in the lattice due to the photoelectric effect, generating many high-energy electrons. Through the elastic collision of large-momentum X-ray photons with small fluoride ions, anionic Frenkel defects are formed in the nanocrystals, capturing thermalized low-energy electrons and enabling long-life capture. Specifically, fluoride vacancies and interstitials are formed as electron traps (E traps) and hole traps (H traps). The displacement of fluoride ions over short and long distances forms transient shallow trap states and long-lived deep trap states, respectively. Over time, electrons in shallow traps can spontaneously escape to the conduction band while undergoing a defect self-healing process, while electrons in deep traps require additional energy from photostimulation or thermal stimulation to migrate to Tb 3+ and Dy 3+ The trapped holes can also migrate to Tb 3+ Emitter, hole formation - Tb 3+ and Dy 3+ Based on the above principle, when an irradiated overdose sheet is measured on a special measuring instrument, the radiation energy stored in the defect is released in the form of visible light after heating the dosimeter, and the intensity of the light is proportional to the received energy.
[0015] Compared with NaLuF4:Tb, NaLuF4:Tb,Dy dose film has higher defect density and greater defect depth, and can more effectively capture and store X-ray energy, so the thermoluminescence brightness is higher and the sensitivity is higher.
[0016] Furthermore, the rare earth salt includes at least one of rare earth nitrates, rare earth chlorides and rare earth acetates.
[0017] Furthermore, the fluoride includes sodium fluoride or a combination of sodium fluoride and ammonium fluoride.
[0018] From the above description, it can be seen that in the process of hydrothermal synthesis of NaLuF4:Tb,Dy, sodium fluoride (NaF) and ammonium fluoride (NH4F) play the following roles respectively: Sodium fluoride: provides the fluoride ions (F - ), participate in the formation of the crystal structure, these fluoride ions and terbium (Tb 3+ ) and lanthanum (Lu 3+ ) and other metal ions to form a NaLuF4 matrix.
[0019] Ammonium fluoride: also provides fluoride ions, while ammonium ions (NH4 + ) In aqueous solution, the pH value of the solution can be adjusted to help control the morphology and size of the crystals and form more uniform nanoparticles. The addition of ammonium fluoride helps to optimize the crystal morphology and product quality.
[0020] Furthermore, when the fluoride is a combination of sodium fluoride and ammonium fluoride, both sodium fluoride and ammonium fluoride are prepared into aqueous solutions, and then mixed with rare earth salt and water; the concentration of the sodium fluoride aqueous solution is 0.1~1 mol / L; the concentration of the ammonium fluoride aqueous solution is 0.5~15 mol / L.
[0021] Preferably, the concentration of the sodium fluoride aqueous solution is 0.5-1 mol / L; the concentration of the ammonium fluoride aqueous solution is 4-5 mol / L.
[0022] From the above description, it can be seen that preparing sodium fluoride and ammonium fluoride into aqueous solutions can ensure that sodium fluoride and ammonium fluoride are fully dissolved, produce high concentrations of fluoride ions, ensure sufficient reaction with metal ions, and provide better reaction conditions. If sodium fluoride and ammonium fluoride powders are used directly, the ions cannot be effectively diffused, and the reaction may be insufficient or uneven.
[0023] The aqueous solution provides a uniform reaction environment, which is conducive to controlling the temperature and pressure of the reaction. Through the dissolution-recrystallization process, the crystals can be promoted to grow in the expected manner to obtain products with uniform particles and controllable morphology.
[0024] Furthermore, the molar ratio of the rare earth salt to sodium fluoride is 1:1-6, and the molar ratio of the rare earth salt to ammonium fluoride is 1:0-9.
[0025] Preferably, the molar ratio of the rare earth salt to sodium fluoride is 1:1-3, and the molar ratio of the rare earth salt to ammonium fluoride is 1:3-5.
[0026] From the above description, it can be seen that the change in the molar ratio between fluoride and rare earth salt will have a significant impact on the crystal structure, size, morphology and luminescence properties of the product. The specific effects are as follows: 1. When the proportion of fluorine source is higher, more F can be provided. - ions promote the full formation of fluoride in the crystal structure, which helps the crystal form a complete NaLuF4 phase structure. However, excessive fluoride sometimes produces byproducts such as sodium fluoride crystals or affects the growth direction of the crystal, resulting in an increase in phase impurities in the product, a relatively low proportion of rare earth doping ions, and affected luminescence intensity.
[0027] 2. If the fluorine ion is insufficient, it will affect the normal growth of NaLuF4 crystals, may produce incomplete crystal phases, and even form undesirable intermediate phases such as LuF3 or TbF3, thereby reducing the quality and luminescence performance of the material. When the fluorine source is insufficient, the morphology and crystallinity of the crystal will deteriorate, affecting the stability and optical properties of the material, making the Tb in the crystal 3+ He Lu 3+ The coordination is incomplete and the distribution of rare earth ions in the crystal is uneven, which in turn affects the activity of the luminescence center, resulting in reduced luminescence efficiency and affecting the optical transparency of the material.
[0028] Furthermore, the molar ratio of sodium fluoride to ammonium fluoride is 1:0-9.
[0029] From the above description, it can be seen that if the proportion of sodium fluoride is high and the proportion of ammonium fluoride is low, the F in the product - The ion source mainly relies on sodium fluoride. Such a system usually produces larger particles and the crystal morphology may be more regular. + With fewer ions, the pH regulating effect is reduced, and the crystal growth rate and morphology may not be uniform, affecting the controllability of the nanomaterial.
[0030] If the proportion of ammonium fluoride is high and the proportion of sodium fluoride is low, NH4 + Ions can better adjust the pH value of the solution, help control the size and morphology of the crystals, and usually produce nanoparticles with smaller size and better dispersion. + The presence of can also promote uniform nucleation, which is beneficial to the formation of monodisperse nanocrystals. However, excessive ammonium fluoride may produce by-products such as ammonium fluoride precipitation.
[0031] Furthermore, the volume ratio of the mixed liquid to the alcohol solvent is 2-5:1.
[0032] Preferably, the volume ratio of the mixed liquid to the alcohol solvent is 3-4:1.
[0033] From the above description, it can be seen that the role of alcohol solvent in the synthesis process is mainly to regulate the polarity of the solution, the reaction rate and the crystal growth. The change in the proportion of alcohol solvent will significantly affect the size, morphology and dispersibility of the nanoparticles. Generally, the right amount of alcohol solvent helps to generate smaller and more uniform nanocrystals, while too much or too little alcohol solvent will lead to abnormal crystal growth or incomplete reaction.
[0034] Furthermore, the alcohol solvent is any alcohol solvent known to those skilled in the art.
[0035] Furthermore, the alcohol solvent is ethanol.
[0036] Furthermore, in S1, a sodium hydroxide aqueous solution is used to adjust the pH value of the mixed solution to neutral.
[0037] From the above description, it can be seen that using sodium hydroxide aqueous solution to adjust the pH value of the mixed solution can avoid the introduction of impurities that affect the purity of the dosage tablets.
[0038] Furthermore, the concentration of the sodium hydroxide aqueous solution is 10-20 mol / L.
[0039] Furthermore, the concentration of the rare earth salt in the rare earth salt solution is 0.5-10 mol / L.
[0040] Preferably, the concentration of the rare earth salt in the rare earth salt solution is 0.8-2 mol / L.
[0041] Furthermore, the rare earth elements in the rare earth salt include lutetium, terbium and dysprosium, and the molar ratio of lutetium, terbium and dysprosium is 3~200:1:0.01.
[0042] Preferably, the molar ratio of lutetium, terbium and dysprosium is 3-6:1:0.01.
[0043] Furthermore, the molar content of terbium in the rare earth salt is 0.5-50%.
[0044] Preferably, the molar content of terbium in the rare earth salt is 5-20%, and the content of dysprosium is 0.1-0.5%.
[0045] From the above description, it can be seen that the change in the molar content of terbium and dysprosium has a significant effect on the luminescence performance, spectral characteristics, crystal structure and energy transfer process. The appropriate doping concentration can optimize the luminescence intensity and color, while too high a doping concentration will lead to a concentration quenching effect, reduce the luminescence efficiency and affect the overall performance of the material. Therefore, the reasonable selection of the doping concentration of terbium and dysprosium is the key to designing high-performance luminescent materials.
[0046] Furthermore, the specific steps of S1 are: adding a rare earth salt to water and ultrasonically mixing for 3 to 10 minutes to obtain a rare earth salt solution, then adding a sodium fluoride aqueous solution to the rare earth salt solution and stirring at a speed of 600 to 1000 r / min for 10 to 40 minutes, then adding an ammonium fluoride aqueous solution and continuing to stir for 20 to 60 minutes, then adjusting the pH value of the mixed solution to neutral and continuing to stir for 10 to 30 minutes, adding an alcohol solvent for hydrothermal reaction, and obtaining a NaLuF4:Tb,Dy powder material.
[0047] Preferably, the specific steps of S1 are: adding a rare earth salt to water and ultrasonically mixing for 3 to 10 minutes to obtain a rare earth salt solution, then adding a sodium fluoride aqueous solution to the rare earth salt solution and stirring at a speed of 800 to 900 r / min for 20 to 30 minutes, then adding an ammonium fluoride aqueous solution and continuing to stir for 30 to 40 minutes, then adjusting the pH value of the mixed solution to neutral and continuing to stir for 10 to 20 minutes, adding an alcohol solvent for hydrothermal reaction, and obtaining a NaLuF4:Tb,Dy powder material.
[0048] From the above description, it can be seen that changes in stirring rate and time will affect the crystal morphology, particle size, dispersibility and reaction efficiency of the material. A higher stirring rate helps to produce uniform and smaller particles, and a proper extension of the stirring time is conducive to full crystal growth and improved product purity. Reasonable selection of stirring rate and time is an important step in optimizing material quality and performance.
[0049] Furthermore, the temperature of the hydrothermal reaction is 160~230℃, and the time is 6~48 h.
[0050] Preferably, the temperature of the hydrothermal reaction is 200-210° C. and the time is 6-12 h.
[0051] From the above description, it can be seen that the use of higher temperatures in hydrothermal reactions is conducive to the rapid growth of crystals, the generation of larger particles, and the improvement of product purity and reaction rate, but too high a temperature may lead to the formation of secondary phases and particle agglomeration.
[0052] Sufficient reaction time is conducive to the full growth of crystals and the complete formation of the crystalline phase, but too long a time may lead to particle agglomeration and side reactions. Reasonable control of time is the key to ensuring product quality and dispersibility.
[0053] Furthermore, during the hydrothermal reaction, the volume of the reaction system solution is 10-80% of the volume of the reactor.
[0054] Preferably, during the hydrothermal reaction, the volume of the reaction system solution is 70-80% of the volume of the reactor.
[0055] Furthermore, after the hydrothermal reaction, centrifugation, washing and drying steps were performed to obtain micron-sized NaLuF4:Tb,Dy powder material.
[0056] Furthermore, at least one of double distilled water, ethanol and toluene is used for washing.
[0057] Furthermore, the drying temperature is 60-70°C.
[0058] From the above description, it can be seen that the change of drying temperature has a significant impact on the particle morphology, crystal structure, chemical composition, physical properties and thermal stability of the material. Reasonable selection of drying temperature is an important factor in ensuring the quality and performance of synthetic materials.
[0059] Furthermore, the crystal structure of NaLuF4:Tb,Dy powder material is hexagonal, the particle size is 0.1~10 μm, and Tb 3+ The doping concentration of Dy is 15~25%. 3+ The doping concentration is 0.1~0.5%.
[0060] From the above description, we can see that Furthermore, NaLuF4:Tb,Dy powder material has fluorescence and long afterglow luminescence phenomenon under X-ray excitation, and the afterglow time is 15 to 30 days.
[0061] Furthermore, S2 is specifically as follows: using a tablet press to press the ground and sieved NaLuF4:Tb,Dy powder material into NaLuF4:Tb,Dy dosage tablets under 5-10 mPa cold isostatic pressing.
[0062] From the above description, it can be seen that the NaLuF4:Tb,Dy powder material prepared by the present invention is not doped with any binder or other solvents, and does not need to be sintered. It can be directly formed into a relatively strong sheet structure that is not easy to fall off or crack under 5-10mPa cold isostatic pressing.
[0063] Furthermore, the shape of the NaLuF4:Tb,Dy dosage tablet is rod-shaped, square-shaped or round-shaped.
[0064] Furthermore, the grinding time in S2 is 6 to 12 hours.
[0065] Furthermore, in S2, a 400-500 mesh filter is used for sieving.
[0066] From the above description, it can be seen that a smaller sieve mesh number will screen out larger particles and obtain a powder with a larger particle size, but the particle distribution may be wider, affecting the uniformity and densification of the material.
[0067] Another technical solution adopted by the present invention is: the NaLuF4:Tb,Dy dosage tablet is prepared by adopting the above-mentioned preparation method of the NaLuF4:Tb,Dy dosage tablet.
[0068] Please refer to Figure 1 and Figure 2 Embodiment 1 of the present invention is: a method for preparing a NaLuF4:Tb,Dy dosage tablet, the steps are as follows: S1. Add 79.8 mmol of lutetium nitrate, 20 mmol of terbium nitrate and 0.2 mmol of dysprosium nitrate powder into deionized water to make the volume to 80 mL, mix by ultrasonic for 5 min until dissolved, and obtain a 1.25 mol / L rare earth salt solution.
[0069] S2. Add 100 mL of 1 mol / L sodium fluoride aqueous solution to the rare earth salt solution, and stir at 600 r / min for 20 min; then add 80 mL of 5 mol / L ammonium fluoride aqueous solution, and stir at 800 r / min for 30 min to obtain a mixed solution; add dropwise 20 mol / L sodium hydroxide aqueous solution to adjust the pH value of the mixed solution to neutral (pH=7), continue stirring for 10 min, add 100 mL of ethanol solvent, continue stirring for 20 min, and obtain a reaction solution.
[0070] S3, the reaction solution was transferred to a 500 mL reactor, and the hydrothermal reaction was carried out at 200 ° C for 12 h. The product obtained by the hydrothermal reaction was centrifuged, washed with double distilled water and ethanol for 3 times, and then dried at 60 ° C for 6 h to obtain NaLuF4:Tb,Dy powder material, see Figure 3 ; Please refer to Figure 4 The crystal structure of NaLuF4:Tb,Dy powder material is hexagonal phase, the particle size is mainly 6 μm, Tb 3+ The doping concentration of Dy is 15~25%. 3+ The doping concentration is 0.1~0.5%; NaLuF4:Tb,Dy powder material has fluorescence and long afterglow luminescence phenomenon under X-ray excitation, and the afterglow time is 15~30 days.
[0071] S4. Take 400 mg of NaLuF4:Tb,Dy powder material and grind it in a ball mill for 6 hours. The parameters of the ball mill are set to 3000 times / min. The ground NaLuF4:Tb,Dy powder material is sieved with a 400-mesh filter. The ground and sieved NaLuF4:Tb,Dy powder material is pressed under 6 mPa cold isostatic pressure for 1 minute using a tablet press to make small round NaLuF4:Tb,Dy dosage tablets with a diameter of 7 mm and a thickness of 2 mm. Figure 5 and 6 ; The dosage tablets are encapsulated in a carbon fiber mold that can be easily worn.
[0072] The NaLuF4:Tb,Dy dosimeter and the conventional LiF:Mg,Cu,P dosimeter (TLD710, Shanghai Risheng Technology Co., Ltd.) were irradiated at 0 kV and 200 μA X-ray dose for 1 min. The test results are shown in Figures 7-9 .Depend on Figures 8 and 9 It can be seen that the thermoluminescence peak temperature of the NaLuF4:Tb,Dy dosing sheet is 85 ℃, the thermoluminescence peak wavelength is 547 nm, and the dose-corresponding linear range of the NaLuF4:Tb,Dy dosing sheet is 10 -7 ~10 Gy, and its sensitivity is about 64 times that of LiF:Mg,Cu,P dosimeter.
[0073] Embodiment 2 of the present invention is: a method for preparing a NaLuF4:Tb,Dy dosage tablet, the steps are as follows: S1. Add 60 mmol of lutetium chloride, 20 mmol of terbium chloride and 0.2 mmol of dysprosium chloride powder into deionized water and make the volume to 160.4 mL. Ultrasonic mixing is performed for 3 min until dissolved to obtain a 0.5 mol / L rare earth salt solution.
[0074] S2. Add 1604 mL of 0.1 mol / L sodium fluoride aqueous solution to the rare earth salt solution, and stir at 800 r / min for 10 min to obtain a mixed solution; add dropwise 10 mol / L sodium hydroxide aqueous solution to adjust the pH value of the mixed solution to neutral (pH=7), continue stirring for 20 min, add 882.2 mL of ethanol solvent, and continue stirring for 20 min to obtain a reaction solution.
[0075] S3. The reaction solution was transferred to a 3L reactor and subjected to a hydrothermal reaction at 160°C for 64 h. The product obtained by the hydrothermal reaction was centrifuged, washed with double distilled water and toluene for three times respectively, and then dried at 65°C for 6 h to obtain NaLuF4:Tb,Dy powder material.
[0076] S4. Take 400 mg of NaLuF4:Tb,Dy powder material and grind it in a ball mill for 8 hours. The ball mill parameters are set to 3000 times / min; the ground NaLuF4:Tb,Dy powder material is sieved, and the filter screen is 450 mesh; the ground and sieved NaLuF4:Tb,Dy powder material is pressurized at 5 mPa cold isostatic pressure for 1 minute using a tablet press to make rod-shaped NaLuF4:Tb,Dy dosage tablets with a diameter of 2 mm, a length of 7 mm, and a thickness of 2 mm.
[0077] Embodiment 3 of the present invention is: a method for preparing a NaLuF4:Tb,Dy dosage tablet, the steps are as follows: S1. Add 4000 mmol of lutetium acetate, 20 mmol of terbium acetate and 0.2 mmol of dysprosium acetate powder into deionized water and adjust the volume to 402.02 mL. Ultrasonic mixing is performed for 10 min until dissolved to obtain a 10 mol / L rare earth salt solution.
[0078] S2. Add 30151.5 mL of 0.8 mol / L sodium fluoride aqueous solution to the rare earth salt solution, and stir at 800 r / min for 40 min; then add 2412.12 mL of 15 mol / L ammonium fluoride aqueous solution, and stir at 1000 r / min for 60 min to obtain a mixed solution; add dropwise 15 mol / L sodium hydroxide aqueous solution to adjust the pH value of the mixed solution to neutral (pH=7), continue stirring for 30 min, add 6593.128 mL of ethanol solvent, and continue stirring for 20 min to obtain a reaction solution.
[0079] S3. The reaction solution was transferred to a 40L reactor and subjected to a hydrothermal reaction at 230°C for 2h. The product obtained by the hydrothermal reaction was centrifuged, washed with double distilled water and ethanol for 3 times respectively, and then dried at 70°C for 5h to obtain NaLuF4:Tb,Dy powder material.
[0080] S4. Take 400 mg of NaLuF4:Tb,Dy powder material and grind it in a ball mill for 12 hours. The ball mill parameters are set to 3000 times / min; the ground NaLuF4:Tb,Dy powder material is sieved, and the filter screen is 500 mesh; the ground and sieved NaLuF4:Tb,Dy powder material is pressurized at 10 mPa cold isostatic pressure for 1 minute using a tablet press to make square NaLuF4:Tb,Dy dosage tablets with a length of 5 mm, a width of 7 mm, and a thickness of 2 mm.
[0081] Embodiment 4 of the present invention is: a dosage tablet prepared by the preparation method of embodiment 1.
[0082] In summary, the NaLuF4:Tb,Dy dose sheet and preparation method thereof provided by the present invention adopt an improved hydrothermal synthesis method to prepare the NaLuF4:Tb,Dy thermoluminescent material, and adopt a tabletting method to produce a solid thermoluminescent dose sheet with excellent performance. The dose sheet has high sensitivity to X-rays and shows extremely excellent sensitivity, which is 64 times the sensitivity of the most common LiF:Mg,Cu,P thermoluminescent dose sheet currently on the market. In addition, the dose sheet also has the advantages of moderate luminescence peak temperature, large linear range, good energy response, simple preparation process, low cost, long-term repeated use, stable luminescence, etc. It has good application value in the field of solid thermoluminescent dose monitoring.
[0083] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a NaLuF4:Tb,Dy dosage tablet, characterized in that: The following steps are involved: S1, mixing a rare earth salt and water to obtain a rare earth salt solution, then mixing the rare earth salt solution with a fluoride to obtain a mixed solution, adjusting the pH value of the mixed solution to neutral, and then adding an alcohol solvent to perform a hydrothermal reaction to obtain a NaLuF4:Tb,Dy powder material; S2. Form NaLuF4:Tb,Dy powder material into sheets to obtain NaLuF4:Tb,Dy dosage sheets.
2. The method for preparing the NaLuF4:Tb,Dy dosage tablet according to claim 1, characterized in that: The rare earth salt includes at least one of rare earth nitrates, rare earth chlorides and rare earth acetates.
3. The method for preparing the NaLuF4:Tb,Dy dosage sheet according to claim 1, characterized in that: The fluoride includes sodium fluoride or a combination of sodium fluoride and ammonium fluoride.
4. The method for preparing the NaLuF4:Tb,Dy dosage tablet according to claim 3, characterized in that: When the fluoride is a combination of sodium fluoride and ammonium fluoride, the sodium fluoride and ammonium fluoride are both prepared into aqueous solutions, and then mixed with rare earth salts and water; the concentration of the sodium fluoride aqueous solution is 0.1-1 mol / L; the concentration of the ammonium fluoride aqueous solution is 0.5-15 mol / L.
5. The method for preparing the NaLuF4:Tb,Dy dosage tablet according to claim 3, characterized in that: The molar ratio of the rare earth salt to sodium fluoride is 1:1-6, and the molar ratio of the rare earth salt to ammonium fluoride is 1:0-9.
6. The method for preparing the NaLuF4:Tb,Dy dosage tablet according to claim 1, characterized in that: The volume ratio of the mixed solution to the alcohol solvent is 2-5:
1.
7. The method for preparing the NaLuF4:Tb,Dy dosage tablet according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 160-230° C., and the time is 2-64 h.
8. The method for preparing the NaLuF4:Tb,Dy dosage tablet according to claim 1, characterized in that: The crystal structure of the NaLuF4:Tb,Dy powder material is hexagonal, the particle size is 0.1-10 μm, and Tb 3+ The doping concentration of Dy is 15~25%. 3+ The doping concentration is 0.1~0.5%.
9. The method for preparing the NaLuF4:Tb,Dy dosage tablet according to claim 1, characterized in that: The S2 is specifically: using a tablet press to press the ground and sieved NaLuF4:Tb,Dy powder material into NaLuF4:Tb,Dy dosage tablets under 5-10mPa cold isostatic pressing.
10. A NaLuF4:Tb,Dy dosage tablet prepared by the method for preparing a NaLuF4:Tb,Dy dosage tablet according to any one of claims 1 to 9.
Citation Information
Patent Citations
Thermoluminescent detection material and preparation method thereof
CN111333422A